Preserving the Modernist Vertical Urban Factory - Rappaport, Nina (Cuaderno de Notas, 2016)
This essay is adapted in part, from the section, “Modern Factory Architecture” case studies from Nina Rappaport’s book Vertical Urban Factory, published by Actar this spring. Vertical Urban Factory began as an architecture studio, and then an exhibition, which opened in New York in 2011 and traveled to Detroit and Toronto in 2012. Last year the show was displayed at Archizoom at EPFL in Lausanne; Industry City, Brooklyn; and the Charles Moore School of Architecture at Kean University, in New Jersey. The project continues as a think tank evaluating factory futures and urban industrial potential.